Materi Pendidikan Agama Kristen Transformasi - Delly Maria Pusung (Sekolah Tinggi Agama Kristen Lentera Bangsa Manado, 2022)
Christian Education always gives an important role in educating and shaping the students who receive the education. The presentation of Christian education materials is expected to be well prepared in teaching. Christian Education Materials must be right on target and able to answer the needs of students. Christian Education materials must be presented by designing it first, whether it still can be taught or it is need to be transformed. This research is referred to knowing the role of Christian education in developing the material in a transformational way. Not only the competence of the educators that is needed in delivering the material, but also to understand correctly what the Bible wants to teach through Christian education materials. The Factors that related to the need of transformational Christian education are seen from the low learning achievement of the students, behavior that deviates from moral standards and the inability to apply Christian values through life and behavior of the students. This research is needed to encourage educational institutions and church institutions to encourage every educator to not only prepare Christian education materials well, but also to transform Christian education materials according to the target, answer the need and can also be accepted at all levels. This research is needed to encourage Christian education to be able to answer problems in the world of Christian education.